Agricultural production and bird conservation in complex landscapes of the dry Chaco - Macchi, Leandro (2015)
The South American dry Chaco is a mosaic of woody vegetation and grasslands with high deforestation rates in recent decades. Considering forests and grasslands as the main natural habitats, we assessed the trade-offs between bird populations and agricultural production to compare the potential consequences of different land use strategies (‘sharing’, ‘sparing’, and intermediate) for populations of bird species sensitive to agriculture, while attaining a regional production target. We evaluated how populations responded to scenarios with different proportions of forest and grasslands, considering three reference states (100% forest, 80:20% and 50:50% forest and grasslands, respectively); and scenarios capable of meeting three after-farming scenarios, with land destined to reach a regional production target with three variations of forest:grasslands within spared land. We fitted curves to relate bird abundance to agricultural yield along a gradient of meat production intensity; and we classified bird species as ‘losers’ (if their populations were lower than the baseline population in the reference state, at any level of production) and ‘winners’ (if their current populations were higher than the baseline population). At the ‘current’ (c. 2010) level of regional agricultural production, we found a similar number of loser species maximized by land-sparing and land-sharing strategies; while intermediate strategies were the least favourable to balance production and bird populations. Under the most probable scenarios of increases in regional meat production, most loser bird species populations were maximized by a land-sparing strategy, suggesting that if meat production targets are going to increase in the region, this can be more efficiently achieved by combining well-protected forests and grasslands, and high-yielding mechanized agriculture (e.g. soybean). Our results highlight the importance of assessing all the important natural habitats (e.g. forests and grasslands) of a region to explore conservation strategies at a regional scale.